Vascular responses to coronary calcification following implantation of newer-generation drug-eluting stents in humans: impact on healing. (5th December 2019) - Torii, Sho; Jinnouchi, Hiroyuki; Sakamoto, Atsushi; Mori, Hiroyoshi; Park, Joohyung; Amoa, Falone C; Sawan, Mariem; Sato, Yu; Cornelissen, Anne; Kuntz, Salome H; Kutyna, Matthew; Paek, Ka Hyun; et al.
Abstract: Aims: Vascular calcification is routinely encountered in percutaneous coronary intervention (PCI) and severe coronary calcification is a known predictor of in-stent restenosis and stent thrombosis. However, the histopathologic mechanisms behind such events have not been systematically described. Methods and results: From our registry of 1211 stents, a total of 134 newer-generation drug-eluting stents (DES) (Xience, Resolute-Integrity, PROMUS-Element, and Synergy) with duration of implant ≥30 days were histologically analysed. The extent of calcification of the stented lesions was evaluated radiographically and divided into severe (SC, n  = 46) and non-severely calcified lesions (NC, n  = 88). The percent-uncovered struts per section {SC vs. NC; median 2.4 [interquartile range (IQR) 0.0–19.0] % vs. 0.0 (IQR 0.0–4.6) %, P  = 0.02} and the presence of severe medial tears (MTs) (59% vs. 44%, respectively, P  = 0.03) were greater in SC than NC. In addition, SC had a higher prevalence of ≥3 consecutive struts lying directly in contact with surface calcified area (3SC) (52% vs. 8%, respectively, P  < 0.0001). Multivariate analysis demonstrated that sections with duration of implantation ≤6 months [odds ratio (OR): 7.7, P  < 0.0001], 3SC (OR: 6.5, P  < 0.0001), strut malapposition (OR: 5.0, P  < 0.0001), and lack of MTs (OR: 2.5, P  = 0.0005) were independent predictors of uncovered struts. Prevalence of neoatherosclerosis was significantly lower in SC than that of NC (24% vs. 44%, P  = 0.02). Conclusion: Severe calcification, especially surface calcified area is an independent predictor of uncovered struts and delayed healing after newer-generation DES implantation. These data expand of knowledge of the vascular responses of stenting of calcified arteries and suggests further understand of how best to deal with calcification in patients undergoing PCI.